2018
DOI: 10.1037/ccp0000303
|View full text |Cite
|
Sign up to set email alerts
|

How do electronic cigarettes affect cravings to smoke or vape? Parsing the influences of nicotine and expectancies using the balanced-placebo design.

Abstract: Findings suggest that cognitive expectancies contribute to the acute effects of e-cigarettes on craving, which may provide guidance for their potential as smoking cessation aids. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 30 publications
1
16
1
1
Order By: Relevance
“…). These findings are consistent with past studies showing that e‐cigarettes are capable of alleviating cigarette withdrawal symptoms following ad‐libitum use . Overall, our data show that e‐cigarettes produce less desirable effects than cigarettes but comparably manage overall withdrawal symptoms.…”
Section: Discussionsupporting
confidence: 93%
“…). These findings are consistent with past studies showing that e‐cigarettes are capable of alleviating cigarette withdrawal symptoms following ad‐libitum use . Overall, our data show that e‐cigarettes produce less desirable effects than cigarettes but comparably manage overall withdrawal symptoms.…”
Section: Discussionsupporting
confidence: 93%
“…Blind studies cannot inform our understanding of naturalistic experiences in which individuals expect that they are consuming or abstaining from an active drug and may fail to identify specific symptoms more likely to manifest under open‐label conditions, such as craving. Indeed, studies with nicotine have demonstrated that craving is strongly influenced by expectancy (Darredeau & Barrett, ; Gu et al, ; Juliano & Brandon, ; Palmer & Brandon, ; Perkins et al, ; Schlagintweit, Good, & Barrett, ). However, our understanding of expectancy influences on craving for drugs other than nicotine is limited.…”
Section: Introductionmentioning
confidence: 99%
“…In caffeine studies abstinence was confirmed by a saliva sample (47,59). In nicotine studies abstinence was confirmed by carbon monoxide sample (49,52,53,55,57,60,62).…”
Section: Description Of Studies Characteristicsmentioning
confidence: 92%
“…Participants in nicotine studies were asked to rate the strength of their cigarettes, e-cigarettes, chewing gum, or spray, except in the study of Schlagintweit et al (57). Participants had to answer if the spray contained nicotine or were asked to estimate the nicotine dose received (49,62) or to answer questions about nicotine sensations (52), to complete a scale of nicotine effect on cognitive performance (53,56) or to fill a questionnaire to evaluate the deception (49,51,60). Table 2 shows the main outcomes of the papers analyzed.…”
Section: Nicotine Studiesmentioning
confidence: 99%
See 1 more Smart Citation